Petrological evidence for isobaric cooling of ultrahigh-temperature pelitic granulites from the Khondalite Belt, North China Craton - Gou, Long-Long; Zhang, C.; Wang, Q. (2015)
© 2015, Science China Press and Springer-Verlag Berlin Heidelberg. The ultrahigh-temperature (UHT) pelitic granulites from the Khondalite Belt, North China Craton (NCC), contain ilmenite in the matrix, which has been partially replaced by rutile. Based on this observation and the growth of biotite by garnet-consuming reaction, the UHT rocks are inferred to have recorded three metamorphic stages: the peak metamorphic stage (M1) and two retrograde metamorphic stages (M2 and M3). The M1 stage is represented by the assemblage of perthite + sillimanite + ilmenite in the matrix, and quartz inclusions bearing (in the cores) garnet porphyroblasts. The M2 stage is defined by rutile-replacing ilmenite and growth of garnet mantles and rims containing acicular sillimanite inclusions, with the garnet + perthite + sillimanite + rutile + ilmenite + quartz assemblage. The M3 stage is recorded by the growth of biotite in the matrix, with the garnet + biotite + perthite + sillimanite + rutile + ilmenite + quartz assemblage. Based on phase equilibrium modeling, an isobaric cooling path is reconstructed, which is consistent with the idea that mantle-derived magma provided the heat for the UHT metamorphism in the Khondalite Belt, NCC.